Practices Towards Electronic Medical Records Implementation at MOI Level 5 Hospital Taita Taveta County. - Omambia, Salim M.; Mbunga, Grace (Advances in Social Sciences Research Journal, 2020)
Electronic Medical Records is the use of information and communication technology (ICT) for health care systems. Although Electronic Health Records has been discoverable for decades, hospitals, doctors and other caregivers have been slow to adopt them. Inadequate use of technology leads to a decrease of provision of service quality. Embracing modern technology is one among very many ways of improving efficiency and reducing costs within healthcare organizations. EMR helps to get rid of missing records, duplication of records, minimize the cost of services, saves time and enhances co-ordination between healthcare providers. Objective: The broad objectives of the study was to practises towards implementation of Electronic Medical Record systems at Moi Level 5Hospital Taita Taveta County. Methods: This study used descriptive study design. The study population that was used are all health workers that are privy to information that was influencing implementation of EMR. The researcher applied census sampling method where the entire health workers were questioned. A questionnaire was used to collect data. The researcher pre-tested the data collection tool to check on the validity and reliability of the results. The pre-tested data was arranged systematically according to the codes of the questionnaires to facilitate analysis. The researcher used a number of software packages to facilitate data analysis. The software packages include Microsoft word and Microsoft Excels for calculation practices. Also researcher made use of calculator in the study. Results and Discussion:Results show that at Moi hospital 85.25% of the respondents had not received any form of training and only 14.71% had received training, out of the 68 respondents, 86.76% had not received further follow up after the training, and 13.24% received follow up after the training. It was concluded that practices towards EMR implementation were found to influence and correlated to the adoption of EMR. Most healthcare workers reported that they had neither received any form of training nor any further follow-up. The findings indicated a significant positive relationship thus attributing to the low implementation of EMR. It was recommended that including ICT in the curriculum of medical courses as this will give them ownership and confidence to use the technology once they join the practicing field and this will assist in the adoption of EMR by the physicians. After the first formal training of the healthcare practitioners a very good follow-up mentorship should follow to provide the necessary technical support and this will help the healthcare providers to get sufficient experience to be comfortable in the use the EMR system. Conclusions: Organizational factors were an important contributor to implementation of EMR system. The results indicated a significant relationship between the factors and adoption of EMR and this meant that adoption of EMR was affected by organizational factors, practices towards EMR implementation were found to influence and correlated to the adoption of EMR. Most healthcare workers reported that they had neither received any form of training nor any further follow-up. The findings indicated a significant positive relationship thus attributing to the low implementation of EMR. Also, the findings indicated a moderate positive significant relationship between technical factors and adoption of EMR and this meant that adoption of EMR was affected by technical factors. Recommendation: Including ICT in the curriculum of medical courses as this will give them ownership and confidence to use the technology once they join the practicing field and this will assist in the adoption of EMR by the physicians. After the first formal training of the healthcare practitioners a very good follow-up mentorship should follow to provide the necessary technical support and this will help the healthcare providers to get sufficient experience to be comfortable in the use the EMR system. The ministries of health to consider having sufficient health care providers to meet the need of the ever increasing number